Intercellular Transport of Viral Proteins - Simon, Florian; Thoma-Kreß, Andrea (Results and Problems in Cell Differentiation, 2024)
Viruses are vehicles to exchange genetic information and proteins between cells and organisms by infecting their target cells either cell-free, or depending on cell-cell contacts. Several viruses like certain retroviruses or herpesviruses transmit by both mechanisms. However, viruses have also evolved the properties to exchange proteins between cells independent of viral particle formation. This exchange of viral proteins can be directed to target cells prior to infection to interfere with restriction factors and intrinsic immunity, thus, making the target cell prone to infection. However, also bystander cells, e.g. immune cell populations, can be targeted by viral proteins to dampen antiviral responses. Mechanistically, viruses exploit several routes of cell-cell communication to exchange viral proteins like the formation of extracellular vesicles or the formation of long-distance connections like tunneling nanotubes. Although it is known that viral nucleic acids can be transferred between cells as well, this chapter concentrates on viral proteins of human pathogenic viruses covering all Baltimore classes and summarizes our current knowledge on intercellular transport of viral proteins between cells.
CRIS-Team Scopus Importer:2024-09-20
Keywords: Cell-cell communication; Extracellular vesicles; Intercellular transport; Mobile viral protein; Tunneling nanotubes; Viral protein transfer